Properties of radioactive wastes and waste containers. Quarterly progress report, January-March 1980 - Manaktala, H.K.; Weiss, A.J. (Brookhaven National Laboratory, 1980)
Solidification experiments were performed with organic ion-exchange resins using Portland type II cement to investigate waste to binder ratios which result in monolithic waste forms. Test results are provided in tabular form showing formulations which result in considerable swelling, cracking, or splitting of the specimens upon solidification. The range of waste loadings which produce monolithic waste forms is given. Experiments were conducted to establish appropriate waste/binder ratios within which simulated boric acid reactor waste may be incorporated into portland type III cement, to produce acceptable waste forms. Both pH-adjusted and pH-unadjusted boric acid solutions were used. Sodium hydroxide in solid pellet form was used to adjust the boric acid pH. Data are reported for 3, 6, and 12 weight percent boric acid wastes, with pH-adjusted values of 7, 10, and 12. Range of waste/binder ratios investigated is from 0.32 to 1.5. Results are summarized in the form of ternary compositional phase diagrams depicting envelope boundaries within which formulations exhibit no free standing liquids. The cure time is substantially reduced when NaOH pellets are used, rather than 10 M NaOH solution. This is attributed to the higher solid contents in the waste solution when NaOH in solid form is used. A ''two-part'' urea-formaldehyde process was used to solidify four simulated LWR waste streams, viz. ion-exchange bead resins, diatomaceous earth, sodium sulfate, and boric acid wastes. The waste forms were evaluated on the basis of solid monolith, free standing liquid, corrosivity of the free liquids, and specimen shrinkage criteria. The results show that the two-part urea-formaldehyde process (a) is capable of solidifying LWR low-level wastes into solid free-standing monoliths, (b) produces free-standing water with pH approximately 2, and (c) produces specimen shrinkage of approximately 5 volume percent after four weeks in an enclosed environment.